'I can't leave her': Maternal Gothic/Horror in Hereditary (Ari Aster, 2018), Relic (Natalie Erika James, 2020), and You Are Not My Mother (Kate Dolan, 2021) - Quigley, Paula (Routledge, 2025)
If it is the case that Mrs Bates gave birth to the modern American horror film, then her successors continue to disrupt family dynamics in ways that speak to contemporary Western cultural anxieties around the maternal role and its reach. In Relic (Natalie Erika James, 2020), You Are Not My Mother (Kate Dolan, 2021), and Hereditary (Ari Aster, 2018), issues of grief, trauma and mental illness are portrayed as matrilinear as well as intergenerational, and the repressed anxieties that structure the maternal relationship erupt with full force, exposing the often violent contradictions at its root. However, as distinct from films such as The Hole in the Ground (Lee Cronin, 2019) and The Babadook (Jennifer Kent, 2014), which explore maternal ambivalence through the prism of the mother’s suspicion of her male child, these films privilege the daughter’s perspective. Exploring this via the Female Gothic trope of ‘woman plus habitation’1 allows for a visceral interrogation of her conflicted attachment to the corporeal reality of the (ageing) maternal body and her thematically intertwined relationship to the domestic space. Indeed, that these films share this focus, albeit worked through in different ways across a range of national and production contexts, is indicative of the ongoing investment in the mother as one of Western horror cinema’s most enduring – and ‘monstrous’– of figures
The Routledge Companion to Motherhood on Screen
PUBLISHED
London
Keywords: Cinema/Video; Cultural History; Film Studies; Film Theory; Film Theory and Philosophy; Film and Gender; Hollywood Cinema; Theatre/Film Criticism; Visual Arts; gender and feminist media